Baseline Client Interpersonal Agency Moderates the Indirect Effect of Treatment on Long-term Worry in Variants of CBT for Generalized Anxiety Disorder. Issue 6 (November 2019) - Gómez Penedo, Juan Martín; Constantino, Michael J.; Coyne, Alice E.; Romano, Felicia M.; Westra, Henny A.; Antony, Martin M.
Abstract: In a recent trial for generalized anxiety disorder (GAD), cognitive-behavioral therapy (CBT) integrated with motivational interviewing (MI) promoted more long-term worry reduction than CBT alone (Westra, Constantino, & Antony, 2016). A follow-up analysis found that CBT vs. MI-CBT clients evidenced greater increases in friendly submissiveness (FS) across treatment, which in turn promoted lower long-term worry (Constantino, Romano, Coyne, Westra, & Antony, 2018). It was unsurprising that traditional directive CBT promoted more FS than when person-centered MI was integrated; however, given that problematic low agency characterizes GAD, that greater FS promoted better outcome was unexpected. To further unpack this unexpected result, we tested the following moderated mediation hypothesis: for clients with more vs. less problematic low agency at baseline, CBT would still promote more in-session FS than MI-CBT, but this increase would in turn predict increased worry over follow-up. Clients receiving CBT ( n = 43) or MI-CBT ( n = 42) rated their interpersonal problems at baseline and their worry after treatment and across 12-month follow-up. Therapists rated clients' in-session FS multiple times. As predicted, multilevel modeling revealed that for clients with more problematic low agency, CBT vs. MI-CBT facilitated greater FS, which in turn related to increased worry across follow-up. For clients with more problematic high agency, CBT's facilitation of greater FS related to reduced worry across follow-up. A baseline interpersonal problem characteristic of GAD may have implications for treatment matching and for appreciating different pathways to long-term improvement, or deterioration, for different GAD subgroups. Highlights: Client's agency moderates the indirect effect of therapies for generalized anxiety. Submissive clients benefit from reducing in-session friendly-submissive behaviors. Increasing in-session friendly-submissiveness is beneficial for dominant clients.